POLICY IMPLEMENTATION ANALYSIS FREE SMOKE AREAS IN BANDA ACEH CITY - Muazzinah, Muazzinah; Safitri, Winny Dian; Ayubi, Fathurahman Al; Zamharira, Cut; Khalil, Zakki Fuad (Universitas Riau Kepulauan, 2024)
The implementation of the Smoke Free Areas (KTR) policy is felt to be still not optimal in coffee shops in Banda Aceh City, which is a workplace category stipulated in the Banda Aceh City Regulation is Qanun Kota Banda Aceh 5/2016 on Smoke Free Area and Banda Aceh Mayor Regulation. Having the nick name the city of 1000 coffee shops and the average coffee shop customer is an active smoker, KTR should be implemented as a form of creating a good and healthy living environment and protecting public health from the dangers of smoking. This study aims to describe the implementation of the KTR policy at the coffee shops in Banda Aceh City with a qualitative descriptive approach. The data analyze with data collection with in-depth interviews, observation by making more detailed observations at the research location is coffee shops and documentation related to documents and images. Then data reduction which is focused on the process of selecting, simplifying, abstracting and transforming raw data tailored to the needs and focus of the research. Finally, verification and conclusion drawing. The informants in this study consisted of one Head of Banda Aceh City Health Service and one Head of Satpol PP WH City of Banda Aceh, two coffee shop owners and two coffee shop customers. The results showed that the implementation of the KTR policy in coffee shops in Banda Aceh City had not yet obtained maximum results in terms of aspects, namely communication aspects in the form of very less socialization, aspects of budget resources and lack of human resources for the innovation team and bureaucratic aspects despite the existence of derivative regulations from the Qanun namely Banda Aceh Mayor Regulation on Technical Guidelines but there is no SOP for sustainability. The recommendation obtained from this research is that the government needs to conduct a more massive campaign on coffee shops in Banda Aceh City regarding KTR so that owners and customers understand the importance of KTR.